POTENTIAL ANALYSIS AND SUPERVISION OF VAT ON THE UTILIZATION OF DIGITAL CONTENTS (CASE STUDY: STEAM PLATFORM) - Wijaya, Suparna; Naufal Nur Setyo; Waidatin Nur Azizah (Dinasti Publisher, 2020)
Steam is a world-class company for marketing applications and games. The imposition of VAT on steam has become an interesting thing because there has not been a Permanent Establishment in Indonesia till now. The purpose of this study is to describe the VAT funding before and after the establishment of PE on Steam, the constraints of imposing VAT on Steam, and the steps that the Government can take regarding Steam. The research method used is descriptive qualitative. The results of this study prove that when Steam does not have PE in Indonesia, Steam consumers in Indonesia are required to make their VAT for the use of digital content provided by Steam. However, if BUT already exists for Steam, Steam will become a Taxable Entrepreneur (PKP), which is obliged to collect VAT on the delivery of intangible taxable goods or services provided. This certainly makes it difficult in terms of supervision because it is very difficult for the Directorate General of Taxes to supervise anyone, what is the Taxpayer Identification Number.